Analysis of the influence of inflation on consumer purchase interest at the Ansha Aesthetic Beauty Clinic - Novianti, Diah Ayuning; Priyambada, Bagus Bimma; Albart, Nicko (Goodwood Publishing, 2025)
Purpose: This study aims to determine the effect of perceptions of inflation on consumer purchasing interest in beauty services at the Ansha Aesthetic Clinic. This study was conducted to answer the question of whether inflation affects consumer decisions in using aesthetic services. Methodology: This study was conducted at Ansha Aesthetic Clinic, Jakarta, using a quantitative approach with a survey method. The data collection instrument was a questionnaire distributed to 50 respondents who were active and potential consumers of the clinic. The analysis method used was simple linear regression with the help of IBM SPSS Statistics software version 26. Results: The results of the study indicate that perceptions of inflation have a positive and significant effect on consumer purchasing interest. The R Square value of 0.689 indicates that 68.9% of the variation in consumer purchasing interest can be explained by perceptions of inflation. The t-test produces a significant value (p <0.05), which confirms that the effect is statistically significant. This finding provides novel evidence that inflation is not merely a macroeconomic concern but also a direct psychological driver of consumer behavior. Conclusions: The study concludes inflation doesn’t always reduce purchasing interest; middle-upper consumers maintain strong demand for aesthetic services despite price pressures. Limitations: This study at one Jakarta beauty clinic with limited respondents requires cautious generalization due to restricted scope and sample size. Contribution: This study highlights consumer behavior under economic pressure, offering insights for beauty industry, service marketers, and marketing researchers.